GROWTH PORTFOLIO ASSESSMENT: IMPLEMENTASI DALAM PEMBELAJARAN METODOLOGI PENELITIAN - Sukmawati Sukmawati (STKIP Andi Matappa, 2023)
Mastery of research methodology is still one of the causes for students exceeding the normal study period. Effective assessment is required to measure the courseâ€™s learning outcomes. The purpose of this study was to examine the effect of growth portfolio assessment (GPA) on students' abilities using research methodology. This study used an experimental research method with a 2Ã—2 factorial design by giving growth portfolio assessment treatment to the experimental class and test assessment to the control class. The research subjects were Mathematics Education students at the Universitas Muhammadiyah Makassar. Data were collected using validated tests and questionnaires. The data analysis technique used a two-way analysis of covariance (ANCOVA) with covariates of pre-test ability and creativity as moderator variables. The research subjects were Mathematics Education students of Universitas Muhammadiyah Makassar. Data were collected using validated tests and questionnaires. The data analysis technique used a two-way analysis of covariance (ANCOVA) with covariates of pre-test ability and creativity as moderator variables. Students who have low creativity and are assessed by growth portfolios have higher research methodology skills than students who are assessed by test assessment after controlling for initial ability. Students who have high creativity and are assessed with the research methodology ability test assessment are higher than students who are assessed with the growth portfolio, after controlling for initial ability. The results of this study indicate that growth portfolio assessment is well used in learning Research Methodology courses for students who have low creativity and assessment tests for students who have high creativity.